The first integral method for the perturbed Wadati-Segur- Ablowitz equation with time dependent coefficient - INC, MUSTAFA; KILIC, BULENT (Kuwait Journal of Science, 2015)
The first integral method (FIM) is used to construct traveling wave solutions ofperturbed Wadati-Segur-Ablowitz (pWSA) equation with time dependent coefficient inthis manuscript. We obtained some different solutions by using Gauge transformationwith time dependent coefficient of variable transformations. The method is aneffective method to construct the different types of exact solutions of nonlinear partialdifferential equations (NPDE).